Histopathological analysis of tumours and tumour-like lesions of colon and rectum - Vaidhya, Pramila; Adhikari, Ram Chandra; Pant, Anil Dev (Journal of Pathology of Nepal, 2020)
Background: Tumours and tumour like lesions of the colon and rectum have overlapping clinical presentation and may be difficult to diagnose on clinical grounds alone. Histopathological examination although helpful to arrive at correct diagnosis, at times may be difficult and may require ancillary tests such as immunohistochemistry. Materials and Methods: A prospective cross sectional study enrolled 125 cases of colorectal biopsies after histopathological confirmation of tumours and tumour like lesions. The specimens were received at the Department of Pathology, of TUTH, from December 1, 2015 to November 30, 2016. Results: Out of 125 cases, 32 cases were benign tumours, 36 cases were malignant tumours and 57 cases were tumour like lesions. Most common age range was 51-60 years with mean age of 38 years. Males comprised 76.74% and females 23.26% with ratio of 3:1. Juvenile polyp was the commonest lesion. Among benign tumours, tubular adenoma was the most common (19.2%), adenocarcinoma was most common malignant tumour (25.6%) and juvenile polyp was the most common tumour like lesion (27.2%). Left side was most common side (66.67%) and rectum was the most common site (48.8%). Conclusions: The commonest indications for colorectal biopsies were tumours and tumour like lesions. Juvenile polyp was the most common tumour like lesion, tubular adenoma was the most common benign tumour and adenocarcinoma was the most common malignant tumour. Histopathological examination is a gold standard for confirmation of all tumour and tumours like lesions of colon and rectum.